From Opposition to Collaboration: The Evolution of Participatory Culture in The LinaBell IP Generation - Liu Yi; Chen Rui (Mandarinable: Journal of Chinese Studies, 2024)
The rapid rise of LinaBell has been a carnival driven by online user participation. It not only reflects the active agency and creative initiative of audiences in participatory culture but also advances the development of participatory texts, transforming the relationship between producers and recipients from opposition to collaboration. Throughout this process, both parties benefit and fulfill their respective needs. Creators generate higher commercial value with lower production costs, while recipients experience immersive and interactive aesthetic enjoyment through their engagement. The success of LinaBell popularity is also related to the unique form of fan culture in China. Furthermore, it ingeniously addresses the long-standing copyright issues that have hindered user participation in creative processes. However, it is important to acknowledge that this type of storyless intellectual property (IP) has both advantages and limitations.